Correct ou incorrect ? la casuistique de « not at home » dans The Egoist, de George Meredith - Jacqueline Fromonot (Cahiers Victoriens et Edouardiens)
19th-century high life is characterized by a marked attempt at avoiding behavioural mistakes or social blunders, in accordance with courtly ideals of the past. Thus exchanges are over-codified, as is borne out by the use of the conventional phrase « Not at home ». In The Egoist, the expression does not imply that Willoughby is absent, but it simply stands as a correct, polite refusal to see a relation, Lieutenant Patterne. However, the gap between the two strata of meaning cannot be perceived by Patterne, who is unfamiliar with the complexities of etiquette. By constantly shifting view-points in the fictional situations he has created, Meredith shows that the apparent correctness of a statement reveals a type of incorrectness by writing the casuistry which makes it possible to revisit a dead metaphor and study it in the light of truth, truthfulness and deception. With the help of pragmatics and analyses of contemporary philosophers of language like John Austin and Herbert Paul Grice, I examine the concepts of correctness and incorrectness, as well as those of illusion, truth, reality — and disillusionment.